118 Undefined left ventricular arrhythmogenic cardiomyopathy: the value of genotyping and histological characterization. (8th December 2021) - Peretto, Giovanni; Casella, Michela; Merlo, Marco; Rizzo, Stefania; Cappelletto, Chiara; Russo, Antonio Dello; Basso, Cristina; Bella, Paolo Della; Sinagra, Gianfranco; Sala, Simone
Abstract: Aims: Etiology identification and risk stratification represent major issues for patients presenting with undefined left ventricular arrhythmogenic cardiomyopathy (ULVACM). To investigate the role of genotyping and histology for ULVACM classification, management, and risk assessment. Methods and results: We retrospectively analysed a multicentre cohort of patients (screened n  = 1037) with ULVACM defined by ventricular arrhythmia (VA) onset, nonischaemic late gadolinium enhancement (LGE) limited to the LV, and no manifest dilated cardiomyopathy (LVEF ≥ 40%). We selected patients undergoing both next generation sequencing (NGS) genotyping and endomyocardial biopsy (EMB) for etiology definition. When feasible, immunosuppressive therapy (IST) was used to target active myocardial inflammation (AMI). The study endpoint was a composite of cardiac death, heart transplantation and malignant VAs (VT, VF, appropriate ICD treatment). The study cohort is composed by 135 ULVACM patients (age 43 ± 14 years, 63% males, LVEF 55 ± 7%). NGS identified pathogenic or likely-pathogenic variants (PVs/LPVs) consistent with ACM in 21 cases (16%), whereas EMB showed AMI in 78 patients (58%), including 13/21 PVs/LPVs + (62%). IST was started in 41/78 AMI patients (53%), including 9/13 PVs/LPVs + (69%). Twenty patients (15%) met the study endpoint by 12 months, and 36 (27%) by the end of the study (60 ± 27 months). Beyond malignant VT onset, AMI was the only predictor of events by 12 months (HR: 5.0, 95% CI: 1.4–18.1, P  = 0.007). No prognostic role was found for PVs/LPVs, except for the subgroup ( n  = 77) with nonsustained VT onset. Among AMI patients, those treated by IST had a significantly lower occurrence of events, both by 12-months (1/41 vs. 16/37, P  < 0.001) and later (HR: 0.05, 95% CI: 0.01–0.21, P  < 0.001). Results were independently confirmed in PVs/LPVs+ and PVs/LPVs- cases. Excluding the IST population, the association of multiple factors among VT onset, PVs/LPVs, and AMI, resulted in an improved discrimination of arrhythmic risk profiles. Conclusions: Despite its limited diagnostic yield, the combined genetic and histological workup substantially contributed into ULVACM prognostic assessment. Furthermore, EMB identified suitable candidates for IST, who showed better outcomes irrespectively of their genotype.